Optical Trapping and Optical Micromanipulation XIV 2017
DOI: 10.1117/12.2275944
|View full text |Cite
|
Sign up to set email alerts
|

Microrheometric upconversion-based techniques for intracellular viscosity measurements

Abstract: Rheological parameters (viscosity, creep compliance and elasticity) play an important role in cell function and viability. Proc. of SPIE Vol. 10347 103471S-1 upconverting particle inside the trap. Moreover, numerical calculations and experimental data allowed to use the rotation dynamics of the optically trapped upconverting particle for environmental sensing. In particular, the cytoplasm viscosity could be measured by using the rotation time and thermal fluctuations of an intracellular optically trapped upcon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In several studies, cell stretch experiments were conducted by displacing beads attached to the opposite sides of a cell membrane via the optical tweezers [66,67]. The optical tweezers were also used to apply forces or displacements to subcellular structures by modulating beads embedded within cells [66,68].…”
Section: Rheological Measurement Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…In several studies, cell stretch experiments were conducted by displacing beads attached to the opposite sides of a cell membrane via the optical tweezers [66,67]. The optical tweezers were also used to apply forces or displacements to subcellular structures by modulating beads embedded within cells [66,68].…”
Section: Rheological Measurement Techniquesmentioning
confidence: 99%
“…A study using wire-based rotational magnetic spectroscopy demonstrated that cytoplasm of fibroblasts and human cancer cells behave like a viscoelastic fluid rather than an elastic gel [74]. In addition, optical tweezers that can rotate particles trapped within a cell were employed to measure intracellular viscosity [68]. The static and dynamic viscosities were determined based on the rotational velocity or rotational displacement of the particles.…”
Section: F-actinmentioning
confidence: 99%